Degradação de petróleo por isolados de rizóbios da Amazônia. - Britocáuper, Luciana Lima de (2013)
Petroleum is a complex mixture of hydrocarbons. Environmental contamination by this substance and its derivatives causes great ecological impact and the techniques for their remediation has received attention in the recent decades. For decontamination of sites, bioremediation uses microorganisms indigenous or alien, and employment in these remediation of impacted environments requires mechanisms to stimulate and develop the microbial activity in the degradation of petroleum compounds. This project aimed to test rhizobial isolates in the degradation of petroleum compounds. We used a plate scribing method, with petroleum as a carbon source, and then it was verified the ability of microorganisms to degrade hydrocarbons by the technique of the redox indicator, 2,6- dichlorophenol indophenol by DCPIP color change of the blue (oxidised) to colorless (reduced). 120 isoldos of rhizobia, 120 showed the ability to tolerate the presence of oil in the middle, showing good growth when subjected for 15 days in the presence of this substance. Of these 93 isolates, 36 had the ability to use oil as a carbon source for growth scores reached suggested (3,06) with six days of growth. The test of DCPIP, 26 isolates showed partial discoloration, almost complete or complete with six days of observation. From this test, 15 were selected rhizobia was examined in which the potential of the emulsification index and found to be high emulsifying activity / O using the carbon sources petroleum and toluene, using mineral salts media and YM INPA with respect to all the microorganisms and the emulsifying activity O / A, five had high emulsifying activity with oil and five toluene, two had moderate with oil and two with toluene and the rest were low for both sources carbon. These results demonstrate that rhizobia can become a feasible and safe alternative for bioremediation of soils contaminated with this product widely used in global economic sustainability